2019
DOI: 10.7759/cureus.5722
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Psychological Impact of Acne Vulgaris in Female Undergraduate Medical Students of Rawalpindi and Islamabad, Pakistan

Abstract: Background:Acne vulgaris is a common skin disease, affecting approximately 9.4% of the world’s population, with considerable effect on the quality of life. According to a previously conducted study, the prevalence rate of acne in Pakistan was found to be 5%. And to this date, no reliable data is available about the prevalence of acne in Rawalpindi and Islamabad, Pakistan.ObjectivesTo determine the prevalence of acne vulgaris and its psycho-social impact on female undergraduate medical students of Rawalpindi an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 18 publications
(27 reference statements)
0
21
0
Order By: Relevance
“…This may embarrass the affected individual, lower their self-esteem and the overall quality of life, and in worst cases, lead to depression. In adolescents, the prevalence of acne ranges from about 40% to 90% [ 3 , 4 ], and less than 1% to 22% in the general population [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may embarrass the affected individual, lower their self-esteem and the overall quality of life, and in worst cases, lead to depression. In adolescents, the prevalence of acne ranges from about 40% to 90% [ 3 , 4 ], and less than 1% to 22% in the general population [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other research has indicated that people with acne have difficulties in emotion regulation [ 14 ]. Furthermore, greater acne severity is significantly associated with lower quality of life and social functioning [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In women, skin lesions appear most often on the face, which may significantly impact patients’ well-being [ 2 , 3 , 4 , 5 ]. Among female medical students, approximately 61% complained that their acne treatment was a problem, and almost 90% reported that acne impacts their psychosocial functioning [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acne vulgaris (often called acne) is one of the most common in ammatory cutaneous disorders among adolescents and young adults which affects the pilosebaceous unit(1), and could lead to depression, low self-esteem and have adverse in uences on quality of life. In adolescents, it is estimated that the incidence of acne ranges from about 40-90% (2,3). The incidence of acne has been estimated to be 9.4% by the Global Burden of Disease project, ranking it as the eighth most frequent disease worldwide (4).…”
Section: Introductionmentioning
confidence: 99%